Development of Visual Basic Application Based Learning Media On Flat Building Materials - Sari, Indah Puspita; Nurjaman, Adi (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to produce learning media based on a visual basic application of triangles and rectangles. This research is research and development. The method used in this research is a research and development method with a 4-D model (Four-D Model). This development model is modified into 3-D, only until the development stage (Develop). The instrument used in this study was a questionnaire used to assess the validity and practicality of the teaching materials. The validity questionnaire was given to 2 experts in the field of mathematics education and media while the practicality questionnaire was given to students. This research produces learning media based on a visual basic application that is valid, very practical, and effective for use in learning